Plated steel sheet having excellent corrosion resistance and bendability and method for manufacturing the same

CN122959652APending Publication Date: 2026-10-23POHANG IRON & STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611252646.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-09-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]另外,Zn-Mg-Al系锌合金镀覆钢板的情况下,通常经过加工并使用,由于在镀层内包含大量硬度高的金属间化合物,因此存在弯曲加工时在镀层内引起裂纹等弯曲加工性变差的缺点

Benefits of technology

根据本发明的一个方面,可以提供一种耐蚀性和弯曲性优异的镀覆钢板及其制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application provides a Zn-Mg-Al series plated steel sheet having excellent corrosion resistance and bending property and a manufacturing method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-reference to related applications

[0001] This application is a divisional application of Chinese Patent Application No. 2022800663784, filed on September 27, 2022, entitled "Coated Steel Sheet with Excellent Corrosion Resistance and Bending Properties and a Method for Manufacturing the Same Thereof". This application claims priority to KR 10-2021-0130130 (September 30, 2021). Technical Field

[0002] This invention relates to a highly corrosion-resistant coated steel sheet with excellent corrosion resistance and bending properties, and a method for manufacturing the same. Background Technology

[0003] Zinc-coated steel sheets possess the sacrificial corrosion protection characteristic of zinc, which has a lower oxidation-reduction potential than iron, being corroded first when exposed to corrosive environments, thus inhibiting the corrosion of the steel. Furthermore, the zinc coating oxidizes and forms a dense network of corrosion products on the steel surface, isolating the steel from the oxidizing atmosphere and thereby improving its corrosion resistance. Due to these advantageous properties, the application of zinc-coated steel sheets has expanded in recent years to include building materials, household appliances, and automotive steel sheets.

[0004] However, due to increased air pollution caused by industrialization and the gradual deterioration of the corrosive environment, as well as due to strict regulations on resource and energy conservation, the necessity to develop a steel with superior corrosion resistance compared to existing galvanized steel sheets has increased.

[0005] To address this issue, extensive research is underway on manufacturing technologies for zinc alloy-coated steel sheets that incorporate elements such as aluminum (Al) and magnesium (Mg) in the zinc plating bath to enhance the corrosion resistance of the steel. Representative examples include Zn-Mg-Al zinc alloy-coated steel sheets, where Mg is further added to the Zn-Al plating composition.

[0006] In addition, in the case of Zn-Mg-Al zinc alloy coated steel sheets, after processing and use, due to the presence of a large number of high-hardness intermetallic compounds in the coating, there is a disadvantage of poor bending workability, such as cracks caused in the coating during bending processing.

[0007] In addition, during the process of introducing Zn-Mg-Al zinc alloy coated steel sheets into the plating bath and coating them, oxides such as slag may adhere to them, or the reactivity with the steel sheet may be weakened, which may result in poor coating adhesion.

[0008] Therefore, to date, no technology has been developed that can meet the advanced requirements of excellent corrosion resistance, flexibility, and coating adhesion.

[0009] (Patent Document 1) Korean Publication No. 2010-0073819 Summary of the Invention

[0010] Technical problems to be solved According to one aspect of the present invention, a coated steel sheet with excellent corrosion resistance and bending properties and a method for manufacturing the same are provided.

[0011] Furthermore, according to another aspect of the present invention, a coated steel sheet having not only excellent corrosion resistance and bending properties, but also excellent coating adhesion, and a method for manufacturing the same are provided.

[0012] The technical problem addressed by this invention is not limited to the above-described contents. Those skilled in the art can readily understand the additional technical problems of the invention from the full text of this specification.

[0013] Technical solution One aspect of the present invention provides a coated steel sheet comprising: a base steel sheet; and a Zn-Mg-Al coating disposed on at least one side of the base steel sheet, wherein the coating comprises a MgZn2 phase and a Zn single phase formed along the contour line of the MgZn2 phase.

[0014] Another aspect of the present invention provides a method for manufacturing a galvanized steel sheet, comprising the steps of: immersing a base steel sheet in a galvanizing bath for hot-dip galvanizing to meet the requirements relative to the galvanizing bath temperature (T). B ) of T B +10℃ to T B The rolling temperature is +50°C. The plating bath contains, by weight %: Mg: 4.0-7.0%, Al: 11.0-19.5%, with the balance being Zn and other unavoidable impurities. The hot-dip galvanized steel sheet is air-wiped with an inert gas to satisfy the following relationship 1. The air-wiped steel sheet is then cooled to the solidification termination temperature at an average cooling rate of 2-5°C / second.

[0015] [Relation 1] 0.005≤P 空气(air) / (W 空气 ×T) (In the relation 1, the W) 空气 The gap of the air knife is indicated in mm. The P... 空气 The pressure of the air knife is expressed in kPa. T represents the temperature of the supplied inert gas, expressed in °C. Beneficial effects According to one aspect of the present invention, a coated steel sheet with excellent corrosion resistance and bending properties, and a method for manufacturing the same, can be provided.

[0016] Furthermore, according to another aspect of the present invention, a coated steel sheet having not only excellent corrosion resistance and bending properties, but also excellent coating adhesion, and a method thereof for manufacturing the same, can be provided.

[0017] The various advantages and effects of the present invention are not limited to the above description. The various advantages and effects of the present invention will be more easily understood in the process of describing the specific embodiments of the present invention. Attached Figure Description

[0018] Figure 1 This is a photograph showing the surface of the coated steel sheet obtained from Example 1 magnified 1500 times and taken using a field emission scanning electron microscope (hereinafter referred to as "FE-SEM").

[0019] Figure 2 This is a photograph showing the surface of the coated steel sheet obtained from Example 3, magnified 5000 times and taken using a field emission scanning electron microscope (FE-SEM).

[0020] Figure 3 This is a photograph showing the surface of the coated steel sheet obtained from Example 4, magnified 5000 times and taken using a field emission scanning electron microscope (FE-SEM).

[0021] Figure 4 This is an enlarged view of the above. Figure 3 The square marking shown. Best practice

[0022] The terminology used in this specification is for describing specific embodiments and is not intended to limit the invention. Furthermore, unless the opposite meaning is clearly indicated in the relevant definitions, the singular forms used in this specification also include the plural forms.

[0023] The use of "includes" or "includes" in the specification means to specify the composition, not to exclude the existence or addition of other compositions.

[0024] Unless otherwise defined, all terms used in this specification, including technical and scientific terms, shall have the same meaning as commonly understood by those skilled in the art. Terms defined in dictionaries shall be interpreted as having the meaning consistent with the relevant technical literature and currently disclosed content.

[0025] The following is a detailed description of a [coated steel sheet] according to one aspect of the present invention. Unless otherwise specifically defined, the content of each element is expressed in weight % in the present invention.

[0026] In existing technologies for Zn-Mg-Al zinc alloy coated steel sheets, Mg is added to improve corrosion resistance. However, when too much Mg is added, the generation of plating bath dross increases, requiring frequent dross removal. Therefore, the upper limit of Mg addition is limited to 3%.

[0027] Therefore, studies were conducted to further improve corrosion resistance by increasing the amount of Mg added to more than 3%. However, as the amount of Mg added increases, the coating contains a large number of intermetallic compounds with high hardness, which leads to problems such as deterioration of bending properties (or bending workability) during bending processing, such as cracks in the coating.

[0028] Not only is there the issue of bending, but also the poor adhesion of the Zn-Mg-Al zinc alloy coated steel sheet due to the presence of Mg-based slag.

[0029] Therefore, in the prior art, it is technically difficult to provide a coated steel sheet that ensures both corrosion resistance and excellent bending and coating adhesion.

[0030] In order to solve the above problems and provide a coated steel sheet that not only has excellent corrosion resistance but also excellent flexibility and / or coating adhesion, the inventors conducted in-depth research and found that not only the composition of the coating is an important factor, but also the Zn single phase formed along the contour line of the MgZn2 phase formed in the coating is an important factor, thus completing the present invention.

[0031] Therefore, the composition of coated steel sheets that have excellent corrosion resistance as well as excellent weldability and / or chemical treatment properties is described in detail below.

[0032] First, the coated steel sheet according to the present invention comprises: a base steel sheet; and a Zn-Mg-Al coating disposed on at least one side of the base steel sheet.

[0033] The type of base steel plate is not particularly limited in this invention. For example, the base steel plate can be an Fe-based base steel plate commonly used as the base steel plate for galvanized steel plates, i.e., it can be a hot-rolled steel plate or a cold-rolled steel plate, but it is not limited thereto. Alternatively, the base steel plate can also be, for example, carbon steel, ultra-low carbon steel, or high manganese steel used as building materials, home appliance materials, or automotive materials.

[0034] However, as an example, the base steel plate may contain the following composition by weight percent: C: more than 0% (more preferably more than 0.001%) and less than 0.18%, Si: more than 0% (more preferably more than 0.001%) and less than 1.5%, Mn: 0.01-2.7%, P: more than 0% (more preferably more than 0.001%) and less than 0.07%, S: more than 0% (more preferably more than 0.001%) and less than 0.015%, A l: more than 0% (more preferably more than 0.001%) and less than 0.5%; Nb: more than 0% (more preferably more than 0.001%) and less than 0.06%; Cr: more than 0% (more preferably more than 0.001%) and less than 1.1%; Ti: more than 0% (more preferably more than 0.001%) and less than 0.06%; B: more than 0% (more preferably more than 0.001%) and less than 0.03%; the balance being Fe and other unavoidable impurities.

[0035] Although not specifically limited, according to one embodiment of the present invention, at least one side of the base steel plate may be provided with a Zn-Mg-Al coating composed of a Zn-Mg-Al alloy. The coating may be formed only on one side of the base steel plate, or it may be formed on both sides of the base steel plate. In this case, the Zn-Mg-Al coating refers to a coating containing Mg and Al, and primarily containing Zn (i.e., containing more than 50% Zn).

[0036] Although not specifically limited, according to one embodiment of the present invention, the thickness of the Zn-Mg-Al coating can be 5-100 μm, more preferably 10-90 μm. When the coating thickness is less than 5 μm, the coating may be too thin in some areas due to errors caused by thickness deviations, thus potentially reducing corrosion resistance. When the coating thickness exceeds 100 μm, the cooling of the hot-dip coating may be delayed, and as an example, there is a possibility of solidification defects such as flow lines forming on the coating surface. The productivity of the steel sheet may be reduced in order to solidify the coating.

[0037] Furthermore, although not specifically limited, according to one specific embodiment of the present invention, an Fe-Al inhibitory layer may be further included between the base steel plate and the Zn-Mg-Al coating. The Fe-Al inhibitory layer is a layer mainly comprising intermetallic compounds of Fe and Al (e.g., more than 60%), such as FeAl, FeAl3, Fe2Al5, etc. In addition, it may also contain, for example, less than 40% of Zn, Mg, or other components derived from the coating. The inhibitory layer is formed by alloying Fe diffused from the base steel plate during the initial coating stage with the plating bath composition. The inhibitory layer can improve the adhesion between the base steel plate and the coating, while simultaneously preventing Fe from diffusing from the base steel plate to the coating. In this case, the inhibitory layer may be formed continuously between the base steel plate and the Zn-Mg-Al coating, or it may be formed discontinuously. In addition to the above description, the same principles generally known in the art apply to the inhibitory layer.

[0038] Although not specifically limited, according to one embodiment of the invention, the thickness of the inhibition layer can be 0.02-2.5 μm. While the inhibition layer serves to prevent alloying and ensure corrosion resistance, its brittleness may affect processability; therefore, the thickness of the inhibition layer can be 2.5 μm or less. However, to achieve the desired effect, it is preferable to control the thickness of the inhibition layer to be 0.02 μm or more. To further improve the above-mentioned effect, the upper limit of the thickness of the inhibition layer is preferably 1.8 μm. Furthermore, the lower limit of the thickness of the inhibition layer can be 0.05 μm. In this case, the thickness of the inhibition layer can refer to the minimum thickness in the direction perpendicular to the interface of the base steel plate.

[0039] Furthermore, although not specifically limited, according to one specific embodiment of the present invention, the Zn-Mg-Al coating may contain, by weight percent: Mg: 4.0-7.0%, Al: 11.0-19.5%, with the balance being Zn and other unavoidable impurities. The specific composition will be described below.

[0040] Mg: ≥4.0% and ≤7.0% Mg is an element that improves the corrosion resistance of coated steel. In this invention, to ensure the desired excellent corrosion resistance, the Mg content in the coating is controlled at 4.0% or higher. Furthermore, adding too much Mg may not only produce slag but also form a large amount of hard MgZn2 phase within the coating, potentially leading to poor flexibility, such as cracks within the coating during bending processes. Therefore, the Mg content is controlled to be below 7.0%.

[0041] Al: Above 11.0% and below 19.5% Generally, while adding more than 1% Mg can improve corrosion resistance, adding more than 2% Mg increases the formation of plating bath dross due to Mg oxidation in the plating bath, thus requiring frequent dross removal.

[0042] Due to this problem, in existing technologies, Mg of 1.0% or more is added to Zn-Mg-Al zinc alloy coatings to ensure corrosion resistance, but the upper limit of Mg content is set at 3.0% and commercialized. However, in order to further improve corrosion resistance, it is necessary to increase the Mg content to 4% or more. However, when the coating contains more than 4% Mg, there is a problem of slag formation caused by the oxidation of Mg in the plating bath. In addition, the adhesion of the coating may deteriorate due to oxide adhesion caused by slag or reduced reactivity with the base steel plate. Therefore, it is necessary to add more than 11.0% Al. However, in order to suppress slag, adding too much Al increases the melting point of the plating bath. As the operating temperature becomes too high, it may cause problems such as corrosion of the plating bath structure and modification of the steel due to high-temperature operation. Therefore, it is preferable to control the upper limit of Al content in the coating to 19.5%.

[0043] Balance Zn and other unavoidable impurities In addition to the composition of the coating described above, the balance may be Zn and other unavoidable impurities. Unavoidable impurities can include all impurities that may be unintentionally introduced during the typical manufacturing process of hot-dip galvanized steel sheets, the meaning of which will be readily understood by those skilled in the art.

[0044] According to the coated steel sheet of the present invention, the coating comprises a MgZn2 phase as a fine microstructure. Furthermore, the coating may also contain various phases such as a Zn single phase, an Al-Zn binary eutectic phase, a Zn-MgZn2-Al ternary eutectic phase, and an Al single phase. In this specification, the MgZn2 phase refers to a phase dominated by MgZn2, and the Zn single phase refers to a phase dominated by Zn, specifically a phase containing 85% or more Zn by weight. In this case, in addition to the Zn component, the Zn single phase may also contain additional components of Al and Mg dissolved in a range of 15% or less. Furthermore, the Al single phase refers to a phase dominated by Al, specifically a phase containing 85% or more Al by weight, but also containing Zn and Mg dissolved in addition to the Al component. Furthermore, the Zn-MgZn2-Al ternary eutectic phase refers to a ternary eutectic phase in which Zn, MgZn2, and Al phases are all mixed together, and the Al-Zn binary eutectic phase refers to a phase in which Al and Zn phases are arranged in an alternating layered or irregular mixed form. It should be noted that the Zn phase included in the ternary eutectic phase is not included in the single Zn phase formed along the contour line of the MgZn2 phase as described later in this specification.

[0045] Furthermore, according to the present invention, the coating comprises a single Zn phase formed along the contour line of the MgZn2 phase. With respect to existing Zn-Mg-Al coated steel sheets, if a large amount of Mg (4% or more) is contained, a large amount of hard MgZn2 phase is formed within the coating, thus causing problems such as reduced flexibility and internal cracking during bending processing.

[0046] Therefore, through in-depth research, the inventors discovered that by precisely controlling the coating composition and manufacturing conditions to form a single Zn phase as a soft phase along the contour line of the MgZn2 phase, which is a hard phase within the coating, a buffering effect can be achieved between the MgZn2 phase and the Zn-MgZn2-Al ternary eutectic phase, thereby improving corrosion resistance while ensuring flexibility.

[0047] Furthermore, regarding coating adhesion, it was found that by forming a single Zn phase as a soft phase along the contour line of the MgZn2 phase, the single Zn phase connects the Zn-MgZn2-Al ternary eutectic phase and the MgZn2 phase, thus improving coating adhesion.

[0048] At this point, the Zn single phase formed within the coating along the contour line of the MgZn2 phase can be identified by taking a photograph of the surface of the coated steel plate using FE-SEM.

[0049] For example, Figure 1The image shown is a photograph taken using FE-SEM at 1500x magnification to observe the surface microstructure of the coated steel sheet obtained from Embodiment 1 of the present invention. Figure 1 It can be confirmed that a single Zn phase exists along the contour line of the MgZn2 phase, which is mainly composed of MgZn2.

[0050] Furthermore, to determine whether the phase formed along the contour line of the MgZn2 phase corresponds to a single Zn phase, cross-sectional photographs taken using the aforementioned FE-SEM can be used, along with energy dispersive spectroscopy (EDS) to distinguish whether the phase formed along the contour line of the MgZn2 phase is a Zn-dominant phase with a Zn weight percentage of 85% or more. Additionally, in this specification, the Zn single phase formed along the contour line of the MgZn2 phase is defined as including both the first and second Zn single phases described later.

[0051] Furthermore, although not particularly limited, according to one specific embodiment of the present invention, selectively, the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase can be 2-7 μm.

[0052] When the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase is less than 2 μm, the adhesion weakens due to insufficient Zn single phase to act as a buffer between the MgZn2 phase and the Zn-MgZn2-Al ternary eutectic phase, potentially causing problems with bending workability and plating adhesion. On the other hand, when the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase exceeds 7 μm, the Zn phase increases excessively, leading to a lack of Mg, which may cause localized corrosion resistance problems. More preferably, to further improve the above effects, the lower limit of the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase can be 5.0 μm, or the upper limit of the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase can be 6.9 μm.

[0053] At this point, the method for measuring the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase is not particularly limited, but the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase can be measured using photographs of the coating surface taken by FE-SEM and EDS, based on the contour line length of the MgZn2 phase of more than 5 μm.

[0054] Furthermore, according to the present invention, two Zn single phases are formed along the contour line of the MgZn2 phase. First, a Zn single phase adjacent to the contour line of the MgZn2 phase and having a Mg solid solubility of less than 4% by weight is formed (hereinafter referred to as the "first Zn single phase"). Then, a Zn single phase adjacent to the first Zn single phase and having a Mg solid solubility of 4% by weight or more is formed (hereinafter referred to as the "second Zn single phase"). To confirm this, Figure 2 The image shown is a photograph taken at 5000x magnification of the surface of the plated steel sheet obtained from Embodiment 3 of the present invention. Figure 2 The region corresponding to A corresponds to the first Zn single phase formed adjacent to the contour line of the MgZn2 phase. Figure 2 The region corresponding to B corresponds to the second Zn single phase formed adjacent to the first Zn single phase.

[0055] Therefore, when measuring the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase, using the above-mentioned FE-SEM photograph, with the contour line length of the MgZn2 phase of 5 μm or more as a reference, the average distance from the contour line of the MgZn2 phase to the Zn single phase with a Mg solid solution content of up to 4% by weight or more (e.g., Figure 2 The average distance from the outline of the MgZn2 phase to the region including the “B” region is defined as the “average thickness of the Zn single phase” mentioned above.

[0056] In addition, although not particularly limited, according to one specific embodiment of the present invention, selectively, the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line of the MgZn2 phase can be 30-98%.

[0057] When the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line is less than 30%, unevenness may occur in ensuring the overall flexibility and adhesion of the steel plate. On the other hand, when the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line exceeds 98%, insufficient corrosion resistance may occur due to the rapid diffusion of corrosion first on the Zn single phase.

[0058] In order to further improve the above-mentioned effect, more preferably, the lower limit of the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line of the MgZn2 phase can be 60%. Alternatively, the upper limit of the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line of the MgZn2 phase can be 90%.

[0059] The method for measuring the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the MgZn2 phase contour line is not particularly limited. However, as an example, it can be obtained by taking a photograph of the surface of the coated steel sheet using FE-SEM and measuring the proportion of the Zn single phase with a Zn content of 85% by weight or more to the length of the MgZn2 phase contour line based on the contour line length of the MgZn2 phase of 5 μm or more. In this case, as described above, the Zn single phase includes both the first Zn single phase and the second Zn single phase.

[0060] Furthermore, although not specifically limited, the inventors, through in-depth research to further improve the properties of interphase adhesion, have confirmed the existence of two types of Zn single phases formed along the contour line of the MgZn2 phase: a Zn single phase with a Mg solid solution rate of less than 4% (first Zn single phase) and a Zn single phase with a Mg solid solution rate of more than 4% (second Zn single phase). However, through repeated research, the inventors have found that among the Zn single phases formed along the contour line of the MgZn2 phase, 1) Zn single phases with a Mg solid solution rate of more than 4% contribute to improving adhesion to the Zn-MgZn2-Al ternary eutectic phase, and 2) Zn single phases with a Mg solid solution rate of less than 4% contribute to improving adhesion to the MgZn2 phase.

[0061] Specifically, although not particularly limited, according to one embodiment of the present invention, selectively, the area ratio of Zn single phases (or, the first Zn single phase) with a Mg solid solution rate of less than 4% by weight relative to the total area of ​​Zn single phases formed along the contour line of the MgZn2 phase can be 10-90%. When the proportion of Zn single phases with a Mg solid solution rate of less than 4% by weight is less than 10%, the effect of improving the adhesion with MgZn2 may be negligible. On the other hand, when the proportion of Zn single phases with a Mg solid solution rate of less than 4% by weight exceeds 1%, localized uneven interphase bonding may occur. To further improve the adhesion between the Zn single phase and the MgZn2 phase, more preferably, the lower limit of the proportion of Zn single phases with a Mg solid solution rate of less than 4% by weight can be 12%, or the upper limit of the proportion of Zn single phases with a Mg solid solution rate of less than 4% by weight can be 75%.

[0062] Furthermore, although not specifically limited, according to one embodiment of the present invention, selectively, the area ratio of the Zn single phase (or, the second Zn single phase) with a Mg solid solution rate of 4% by weight or more can be 10-90% relative to the total area of ​​the Zn single phase formed along the contour line of the MgZn2 phase. When the area ratio of the Zn single phase with a Mg solid solution rate of 4% by weight or more is less than 10%, the effect on improving the connectivity with the Zn-MgZn2-Al ternary eutectic phase may be negligible. On the other hand, when the area ratio of the Zn single phase with a Mg solid solution rate of 4% by weight or more exceeds 90%, localized uneven interphase connectivity may occur. To further improve the adhesion between the Zn single phase and the Zn-MgZn2-Al ternary eutectic phase, more preferably, the lower limit of the area ratio of the Zn single phase with a Mg solid solution rate of 4% by weight or more can be 25%, or the upper limit of the area ratio of the Zn single phase with a Mg solid solution rate of 4% by weight or more can be 88%.

[0063] Therefore, according to a specific embodiment of the present invention, selectively, in terms of area %, the Zn single phase formed along the contour line of the MgZn2 phase comprises: a first Zn single phase with a Mg solid solution rate of less than 4% by weight: 10-90%; and a second Zn single phase with a Mg solid solution rate of 4% by weight or more: 10-90%. The first Zn single phase may be adjacent to the contour line of the MgZn2 phase, or the second Zn single phase may be adjacent to the first Zn single phase. Furthermore, the above description is equally applicable to both the first Zn single phase and the second Zn single phase.

[0064] In this specification, the method for distinguishing between Zn single phases with a Mg solid solution rate of 4% or more and Zn single phases with a Mg solid solution rate of less than 4% by weight can be achieved by measuring the Mg content of the Zn single phase relative to each location using FE-SEM and EDS.

[0065] Furthermore, while the method for measuring the area ratio of Zn single phases with a Mg solid solution content of 4% by weight or more and the area ratio of Zn single phases with a Mg solid solution content of less than 4% by weight is not specifically limited, for example, it can be achieved by taking a photograph of the coating surface using FE-SEM and EDS and measuring the area based on an area of ​​10 μm. 2 The above measurements are performed by obtaining the area % of each Zn single phase relative to all phases of the coating surface.

[0066] However, in this invention, the Zn single phase with a Mg solid solution rate of 4% by weight or more can exist in a shape where all phases are connected, or in an island shape where phases are separated from each other.

[0067] Therefore, with 10μm 2 Based on the area of ​​the above-mentioned coating surface, 1) such as Figure 2As shown, when the Zn single phase (corresponding to region B) with a Mg solid solution rate of 4% or more exists in a completely connected shape, the region from the outline of the MgZn2 phase to the interior region of the Zn single phase with a Mg solid solution rate of 4% or more is regarded as "Zn single phase formed along the outline of the MgZn2 phase", and the area ratio of each Zn single phase (first Zn single phase and second Zn single phase) is measured.

[0068] On the other hand, 2) such as Figure 3 As shown, when the Zn single phase with a Mg solid solution content of 4% or more exists in the form of isolated islands, as... Figure 3 As shown in the square marker section, draw the line with the shortest distance between two adjacent island shapes. Figure 4 The image shows an enlarged photograph of the square marker portion, and... Figure 4 The diagram shows the line drawing the shortest distance between the two islands. Next, as... Figure 3 The diagram shows the line drawing the shortest distance between the outer contour line of the Zn single phase with a Mg solid solution concentration of 4% or more and the aforementioned island shape. Then, the region from the contour line of the MgZn2 phase to the inner region of the connecting line is considered as a "Zn single phase formed along the contour line of the MgZn2 phase," and the area ratio of each Zn single phase (the first Zn single phase and the second Zn single phase) is measured. When there are two or more lines of the shortest distance between the aforementioned island shapes of equal length, the area ratio of each Zn single phase is measured using the line of the shortest distance closest to the contour line of the MgZn2 phase as a reference.

[0069] Next, a method for manufacturing a coated steel sheet according to another aspect of the present invention will be described in detail. However, this does not mean that the coated steel sheet of the present invention must be manufactured by the following method.

[0070] According to a specific embodiment of the present invention, the step of preparing a base steel plate may be further included, and the type of base steel plate is not particularly limited. It may be a conventional Fe-based base steel plate used as a base steel plate for hot-dip galvanized steel plates, i.e., it may be a hot-rolled steel plate or a cold-rolled steel plate, but is not limited thereto. Furthermore, the base steel plate may be, for example, carbon steel, ultra-low carbon steel, or high-manganese steel used as building materials, household appliance materials, or automotive materials, but is not limited thereto. In this case, the above description can also be applied to the base steel plate.

[0071] Next, the prepared base steel plate is immersed in a plating bath for hot-dip galvanizing to meet the requirements relative to the plating bath temperature (T). B ) of T B +10℃ to T BThe rolling temperature is +50°C, and the plating bath contains, by weight %: Mg: 4.0-7.0%, Al: 11.0-19.5%, with the balance being Zn and other unavoidable impurities.

[0072] At this point, the reasons for adding and limiting the content of the components in the above-mentioned plating bath, except for the content of the small amount of Fe that may flow in from the base steel plate, can also be applied to the description of the composition of the above-mentioned coating.

[0073] In addition, to prepare the plating bath with the above composition, composite steel ingots containing specified Zn, Al, and Mg, or Zn-Mg steel ingots or Zn-Al steel ingots containing individual components can be used. To replenish the plating bath consumed during hot-dip galvanizing, the steel ingots are further dissolved and supplied. In this case, it is also possible to choose a method of directly immersing the steel ingots in the plating bath and dissolving them, or to choose a method of dissolving the steel ingots in a separate tank and then replenishing the plating bath with molten metal.

[0074] Furthermore, during the hot-dip galvanizing process, the initial rolling temperature of the base steel plate is controlled to meet the requirements relative to the bath temperature (T). B ) of T B +10℃ to T B The range is +50℃. At this point, although not specifically limited, the stated plating bath temperature (T...) B The temperature can be maintained within the range of 440-500℃. By setting the initial rolling temperature of the plating bath as described above, the interfacial adhesion between the base steel sheet and the coating can be improved.

[0075] Additionally, when the initial rolling temperature of the base steel plate is lower than T... B At +10°C, the improvement in interfacial adhesion is negligible, and the problem of adhering scum may occur. On the other hand, when the initial rolling temperature of the base steel plate exceeds T... B At +50℃, the generation of ash (Zn fumes) increases and is adsorbed onto the steel plate, which may cause problems with the coating surface quality.

[0076] At this point, to further improve the above-mentioned effect, more preferably, the lower limit of the initial rolling temperature of the base steel plate can be T. B +20℃, the upper limit of the initial rolling temperature of the base steel plate can be T B The temperature range is +45℃.

[0077] Next, the hot-dip galvanized steel sheet is air-wiped using an inert gas to satisfy the following relationship 1. By controlling the air-wiping conditions to satisfy the following relationship 1, the single-phase Zn structure formed along the contour line of the MgZn2 phase as specified in this invention is ensured, while smooth and uniform surface properties are also ensured, thereby improving flexibility. Here, the following relationship 1 is an empirically derived value, so the units are not particularly limited, as long as W is satisfied as defined below. 空气 The units are mm and P. 空气 The units are kPa and T, respectively, in °C.

[0078] [Relation 1] 0.005≤P 空气 / (W 空气 ×T) (In the relation 1, the W) 空气 The gap of the air knife is indicated in mm. The P... 空气 The pressure of the air knife is expressed in kPa. T represents the temperature of the supplied inert gas, expressed in °C. In addition, although not particularly limited, according to one specific embodiment of the present invention, the inert gas may be argon (Ar), nitrogen (N2) or a mixture of argon and nitrogen, and nitrogen is more preferably used.

[0079] Furthermore, according to a specific embodiment of the present invention, in the above-described air wiping step, the gap of the air knife can be in the range of 20-45 mm (more preferably 30-40 mm). Alternatively, the pressure of the air knife can be in the range of 8-20 kPa (more preferably 10-18 kPa). Alternatively, the temperature of the supplied gas can be in the range of 30-100°C (more preferably 65-85°C). By adjusting the air wiping conditions to meet the above ranges, a coated steel sheet with excellent corrosion resistance, bending properties, and coating adhesion can be manufactured.

[0080] Subsequently, the air-wiped steel sheet is cooled to the solidification termination temperature at an average cooling rate of 2-5°C / second, based on the surface temperature. During the cooling step after air wiping, if the average cooling rate is less than 2°C / second, the productivity of the coated steel sheet may be problematic; if the average cooling rate exceeds 5°C / second, the single-phase Zn structure formed along the contour line of the MgZn2 phase as specified in this invention may not be produced.

[0081] Furthermore, although not specifically limited, according to one specific embodiment of the present invention, selectively, the cooling can be performed in the following three steps: a first cooling, in which the air-wiped steel plate is cooled at an average cooling rate of 1.0-2.0°C / second in a temperature range below 450°C and above 420°C; a second cooling, in which the steel plate cooled in the first cooling is cooled at an average cooling rate of 2.1-4.0°C / second in a temperature range below 420°C and above 340°C; and a third cooling, in which the steel plate cooled in the second cooling is cooled at an average cooling rate of 5.0-7.0°C / second in a temperature range below 340°C and above 150°C.

[0082] Through in-depth research, the inventors discovered that by performing slow cooling, divided into primary, secondary, and tertiary cooling intervals, and gradually increasing the cooling rate in each interval, the flexibility can be further improved. Specifically, when the average cooling rate during the primary cooling is less than 1.0 °C / s, the productivity of the steel sheet may be problematic. On the other hand, when the average cooling rate during the primary cooling exceeds 2.0 °C / s, problems may arise in ensuring uniform interfacial adhesion between the base steel sheet and the coating. Furthermore, when the average cooling rate during the secondary cooling is less than 2.1 °C / s, the productivity of the steel sheet may be problematic. On the other hand, when the average cooling rate during the secondary cooling exceeds 4.0 °C / s, problems may arise in ensuring adhesion between the MgZn2 and Zn single phases within the coating. Moreover, when the average cooling rate during the tertiary cooling is less than 5.0 °C / s, due to the delayed solidification termination time of the steel sheet, there may be a problem of the coating adhering to the upper roller of the cooling tower. On the other hand, when the average cooling rate during the three cooling cycles exceeds 7.0 °C / s, the adhesion between the Zn single phase and the Zn-MgZn2-Al ternary eutectic phase within the coating may become problematic.

[0083] Furthermore, although not specifically limited, according to one specific embodiment of the present invention, selectively, the cooling process may further satisfy the following relationship 2. By controlling the relationship between the average cooling rate during the three cooling cycles and the average cooling rate during the first and second cooling cycles as described in the following relationship 2, the adhesion between the MgZn2 phase and the Zn single phase, as well as the adhesion between the Zn-MgZn2-Al ternary eutectic phase and the Zn single phase, can be improved, thereby further enhancing the flexibility of the coating.

[0084] [Relationship 2] C1 + C2 ≤ C3 ≤ 1.5 × (C1 + C2) (In Equation 2, C1 represents the average cooling rate [°C / sec] during the first cooling cycle, C2 represents the average cooling rate [°C / sec] during the second cooling cycle, and C3 represents the average cooling rate [°C / sec] during the third cooling cycle.) As described above, by precisely controlling the coating composition and manufacturing conditions, it is possible to effectively provide a coated steel sheet that not only has excellent corrosion resistance, but also excellent flexibility and coating adhesion. Detailed Implementation

[0085] (Example) The present invention will now be described in more detail through embodiments. However, it should be noted that the following embodiments are merely illustrative examples and are not intended to limit the scope of the invention. This is because the scope of the invention is determined by the contents of the claims and the contents reasonably deduced therefrom.

[0086] (Experimental Example 1) Prepare a base steel plate with a thickness of 2mm and a width of 1300mm. The base steel plate has the following composition: C: 0.018%, Si: 0.01%, Mn: 0.2%, P: 0.009%, S: 0.005%, Al: 0.1%, Nb: 0.02%, Cr: 0.2%, Ti: 0.02%, B: 0.015%, with the balance being Fe and impurities.

[0087] The prepared base steel plate is immersed in the plating bath for hot-dip galvanizing under the conditions specified in Table 1. Next, the hot-dip galvanized steel plate is air-wiped using nitrogen (N2) under the conditions described in Table 1, and then cooled under the conditions specified in Table 2.

[0088] [Table 1]

[0089] [Table 2]

[0090] C Average cooling rate up to the solidification termination temperature [°C / second] Test pieces of coated steel sheets obtained by the methods described in Tables 1 to 2 were prepared. The coating was dissolved in hydrochloric acid solution and the dissolved liquid was analyzed by wet analysis (ICP) to measure the composition of the coating, which is shown in Table 3 below (wherein, the balance is Zn and impurities).

[0091] In addition, cross-sectional specimens cut along the thickness direction of the steel plate (i.e., the direction perpendicular to the rolling direction) were manufactured to observe the interface between the coating and the base steel plate. The cross-section was then photographed using SEM, thereby confirming that an Fe-Al inhibitory layer with a thickness of 0.1-1 μm was formed between the base steel plate and the Zn-Mg-Al coating.

[0092] In addition, the surface of the steel plate was magnified 1500 times and photographed using FE-SEM and EDS, and the presence of Zn single phase formed along the outline of the MgZn2 phase is indicated by [○ / ×] in Table 3 below.

[0093] At this point, to determine whether it is a Zn single phase, surface photographs taken using FE-SEM and EDS are used, and the distinction is made based on whether it is a Zn single phase containing more than 85% Zn content (by weight %).

[0094] Furthermore, the average thickness of the Zn single phase formed along the contour line of the MgZn2 phase was measured using FE-SEM based on the 5 μm contour line length of the MgZn2 phase, and is shown in Table 3 below.

[0095] [Table 3]

[0096] ○: A single Zn phase exists along the contour line of the MgZn2 phase. ×: There is no single Zn phase formed along the contour line of the MgZn2 phase. For each embodiment and comparative example, the characteristics were evaluated according to the following criteria, and the evaluation results of each characteristic are shown in Table 4 below.

[0097] <Corrosion Resistance> To evaluate corrosion resistance, the test was conducted using a salt spray tester (SST) based on ISO 14993 and according to the following standards.

[0098] ○: Compared to a Zn coating of the same thickness, the time required for the formation of red rust is more than 30 times but less than 40 times longer. △: Compared to a Zn coating of the same thickness, the time required for red rust to form is more than 20 times but less than 30 times longer. ×: Compared to a Zn coating of the same thickness, the time required for red rust to form is less than 20 times. <Flexibility> To evaluate the cracks in the bending section, the number of cracks within a length of 10 mm was observed using FE-SEM after the material was cut into 30 mm × 100 mm pieces and bent for 3t. The bending performance was evaluated according to the following criteria.

[0099] ◎: Less than 5 ○: 5 or more but less than 10 △: 10 or more but less than 20 ×: 20 or more <Coating Adhesion> To evaluate the coating adhesion, the material was cut into 30mm×100mm pieces, and each piece of coated steel was bent at 180° (0T bending). The area of ​​the piece that was peeled off after being pasted was then measured, and the coating adhesion was evaluated according to the following criteria.

[0100] The evaluation criteria for coating adhesion are as follows: ◎: Area without peeling ○: The area of ​​stripping is greater than 0% and less than 3%. △: The peeling area is 3-10%. ×: The peeling area is more than 10%. [Table 4]

[0101] As can be seen from the experimental results in Table 4, under the conditions of Examples 1 to 5 that meet the coating composition and manufacturing conditions specified in this invention, excellent corrosion resistance, bending properties and coating adhesion were confirmed.

[0102] On the other hand, in cases where one or more of the coating composition and manufacturing conditions specified in this invention are not met, it was confirmed that one or more of the properties of corrosion resistance, bending and coating adhesion are worse than those of Examples 1 to 5.

[0103] (Experimental Example 2) Except for hot-dip galvanizing and air wiping under the conditions in Table 5 below, and then cooling in three steps (one, two, and three times) by controlling the average cooling rate, the coated steel sheet was manufactured using the same method as in Experimental Example 1 above.

[0104] At this point, by performing analysis using the same method as in Experimental Example 1, it was confirmed that a Fe-Al inhibitory layer with a thickness of 0.3 μm was formed between the base steel plate and the Zn-Mg-Al coating.

[0105] In addition, the coating composition, the presence of a single Zn phase along the contour line of the MgZn2 phase, and the average thickness were measured using the same method as in Experimental Example 1, and are shown in Table 7 below.

[0106] In addition, using FE-SEM and EDS, the proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the 10 μm MgZn2 phase contour line was measured by the same method as described above in the specification, and is shown in Table 7 below.

[0107] Furthermore, the area captured using FE-SEM and EDS is 25 μm. 2 Using the coated surface as a reference, the area ratio of Zn single phases with a Mg solid solution rate of 4% or more and the area ratio of Zn single phases with a Mg solid solution rate of less than 4% by weight were measured by the same method as described above in this specification, and these values ​​are shown in Table 7 below.

[0108] Furthermore, the corrosion resistance, bending properties and coating adhesion of the coated steel sheets obtained from the various embodiments and comparative examples were evaluated using the same method as in Experimental Example 1, and are shown in Table 8 below.

[0109] [Table 5]

[0110] [Table 6]

[0111] One cooling Cooling in the temperature range below 450℃ and above 420℃ Secondary cooling Cooling in the temperature range below 420°C and above 340°C Three cooling cycles Cooling in the temperature range below 340°C and above 150°C [Table 7]

[0112] [Table 8]

[0113] As can be seen from the experimental results in Table 8, under the conditions of Examples 6 to 10 that meet the coating composition and manufacturing conditions specified in this invention, excellent corrosion resistance, bending properties and coating adhesion were confirmed.

[0114] Specifically, in Examples 8 to 10, where the cooling process of the three steps specified in this invention was performed, it was confirmed that the bendability was further improved compared to Examples 6 and 7. It is speculated that in Examples 8 to 10, the occupancy and average thickness of the Zn single phase formed along the contour line of the MgZn2 phase are large, resulting in the formation of a large amount of soft Zn single phase around the hard MgZn2 phase, thus leading to superior bendability. Furthermore, it is speculated that Zn single phases with a Mg solid solution content of 4% or higher contribute to improved interphase adhesion with the Zn-MgZn2-Al ternary eutectic phase, while Zn single phases with a Mg solid solution content of less than 4% contribute to improved interphase adhesion with the MgZn2 phase, thus ultimately contributing to improved plating adhesion.

[0115] On the other hand, in Comparative Examples 15 and 16, which did not meet the coating composition and manufacturing conditions specified in the present invention, it was confirmed that one or more of the characteristics of corrosion resistance, bending and coating adhesion were worse than those of Examples 6 to 16.

Claims

1. A galvanized steel sheet, comprising: Foundation steel plate; as well as A Zn-Mg-Al based coating is disposed on at least one side of the base steel plate. The coating comprises a MgZn2 phase and a Zn single phase formed along the contour line of the MgZn2 phase. The coated steel sheet includes an Fe-Al based inhibition layer, which is disposed between the base steel sheet and the Zn-Mg-Al based coating. The coating comprises, by weight percent: Mg: 4.0-7.0%, Al: 11.0-19.5%, balance Zn and other unavoidable impurities.

2. The galvanized steel sheet according to claim 1, wherein, The proportion of the Zn single phase formed along the contour line of the MgZn2 phase to the length of the contour line of the MgZn2 phase is 30-98%.

3. The galvanized steel sheet according to claim 1, wherein, The average thickness of the Zn single phase formed along the contour line of the MgZn2 phase is 2-7 μm.

4. The galvanized steel sheet according to claim 3, wherein, In terms of area %, the Zn single phase formed along the contour line of the MgZn2 phase comprises: a first Zn single phase with a Mg solid solution of less than 4% by weight: 10-90%; and a second Zn single phase with a Mg solid solution of more than 4% by weight: 10-90%.

5. The plated steel sheet according to claim 4, wherein, The first Zn single phase is adjacent to the outline of the MgZn2 phase.

6. A method for manufacturing coated steel sheet, comprising the following steps: The base steel plate is immersed in a galvanizing bath for hot-dip galvanizing to meet the requirements relative to the bath temperature T. B T B +10℃ to T B The rolling temperature is +50℃, and the plating bath contains, by weight %: Mg: 4.0-7.0%, Al: 11.0-19.5%, balance Zn and other unavoidable impurities; The hot-dip galvanized steel sheet is air-wiped using an inert gas to satisfy the following relationship 1; as well as The air-wiped steel plate is cooled to the solidification termination temperature at an average cooling rate of 2-5°C / second. [Relation 1] 0.005≤P 空气 / (IN 空气 ×T) In the relation 1, the W 空气 The P represents the gap of the air knife, in mm. 空气 The pressure of the air knife is expressed in kPa, and T represents the temperature of the supplied inert gas in °C.

7. The method for manufacturing coated steel sheet according to claim 6, wherein, The cooling step includes the following steps: The steel plate, after being wiped by air, is cooled at an average rate of 1.0-2.0℃ / second within a temperature range below 450℃ and above 420℃. Secondary cooling involves cooling the steel plate, which has undergone primary cooling, at an average cooling rate of 2.1-4.0°C / second within a temperature range below 420°C and above 340°C; and The steel plate, which has undergone the second cooling process, is cooled at an average rate of 5.0-7.0℃ / second within a temperature range below 340℃ and above 150℃.

8. The method for manufacturing coated steel sheet according to claim 7, wherein, The cooling step satisfies the following relationship 2: [Relationship 2] C1 + C2 ≤ C3 ≤ 1.5 × (C1 + C2) In Equation 2, C1 represents the average cooling rate during the first cooling cycle, C2 represents the average cooling rate during the second cooling cycle, and C3 represents the average cooling rate during the third cooling cycle. The unit of average cooling rate is °C / second.

Citation Information

Patent Citations

  • Method for automatic controlling acid gas capture process

    KR1020210130130A